SAT0140 Prevalence of Reactivation of Hepatitis B Virus (HBV) in Patients with Resolved Hbv Hepatitis on Immunosuppressive Therapy for Rheumatic Disease: Multicentre Prospective Observational Study in Japan. (15th July 2016) - Fukuda, W.; Hanyu, T.; Katayama, M.; Okada, A.; MIzuki, S.; Miyata, M.; Handa, Y.; Hayashi, M.; Koyama, Y.; Arii, K.; Kitaori, T.; Hagiyama, H.; et al.
Abstract : Background: Although the reactivation of hepatitis B virus (HBV) is recognized as a serious complication in patients with connective tissue disease (CTD) receiving immunosuppressive drugs (ISDs), the incidence and risk factors of reactivation remain controversial. Objectives: We performed a multicentre, observational, prospective study across 16 Japanese Red Cross hospitals to clarify the prevalence and pathophysiology of HBV reactivation in patients with CTD. We report the results of 2-year observations in patients with resolved HBV infection. Methods: Patients with CTD, treated with a dose of ≥5 mg/day prednisolone, and/or synthetic or biological ISDs, with negative HBs antigen and positive anti HBs and/or HBc antibody (Ab), were enrolled. HBV-DNA (RT-PCR) and related data were registered regularly. Results: Among 1040 patients, including 950 rheumatoid arthritis, HBV-DNA was detected in 32 patients (1.75/100 person-years), and >2.1 log copy/ml was observed in 9 cases (0.49/100 person-years) over 1–2 years of observation. None of the reactivated patients, including six treated with a nucleic acid analogue, showed overt hepatitis. Low HBs Ab titres and advanced age seemed to be risk factors for HBV reactivation; however, reactivation was observed in 3 patients with positive HBs Ab and negative HBc Ab. The risk of reactivation among the different types of ISDs was not statistically different. The intervals from the start of ISD to reactivation were longer than previous reports (4–157 months, average 58.9 months). Conclusions: HBV reactivation with ISD was 1.75/100 person-years in CTD patients with resolved HBV infection. Overt hepatitis was observed in none of the reactivated patients, and low HBs antibody titres and advanced age were risk factors for reactivation. Patients with positive HBs Ab and negative HBc Ab are not free from the risk of reactivation of HBV. References: B. J Hepatol 2012: 57. 167–185 Disclosure of Interest: None declared